The Effect of Infographic Media on Environmental Pollution to Increase Student's Learning Motivation - Saleha Putri Liana; Kodri Madang; Riyanto Riyanto (Bioedukasi: Jurnal Pendidikan Biologi, 2023)
This study aims to determine the effect of infographic media on environmental pollution material to increase learning motivation of 10th-grade students SMAN 10 Palembang. To optimize learning process, it’s necessary to use digital learning media like infographics as one of digital learning media to increase students learning motivation. The research method used is a Quasi-Experimental Design using a research design Nonequivalent Control Group Design. The sample selection in this study used the technique of Simple Random Sampling. The learning motivation instrument questionnaire used a Likert scale of 18 valid questionnaires. Consists of 6 learning motivation indicators, teaching skills for extrinsic aspect and interest, curiosity, independence, attention, and pleasure for intrinsic aspect. The average value of the percentage of learning motivation is 75% in the control class and 80% for the experimental class, both the motivational values in the control and experimental classes are in the high category. The value of learning motivation data using t-test and learning outcomes data tested by ANCOVA. The results of the hypothesis test of the percentage value of students' learning motivation with the value asymp.Sig (2-tailed) of 0.028 <0.05, it shows that Ho rejected and Ha is accepted, which means that the infographic media on Environmental Pollution material has a significant effect on the learning motivation of students in class X SMA Negeri 10 Palembang.